A CLINICO-ETIOLOGICAL STUDY OF ADVERSE CUTANEOUS DRUG REACTIONS AT TERTIARY CARE CENTER IN SOUTH INDIA - BHANUSHALI, SWETA PRATAP; J PHULARI, YOGANAND; HIREMATH, RAVISHEKAR N; KANDPAL, RENU; PATEL, PRIYANKA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to study the most common aetiology, different clinical manifestations of adverse cutaneous drug reactions (ACDR), and to assess the association of morphological cutaneous pattern of ACDR and etiological group of drugs. Methods: A cross-sectional, observational study was carried out at dermatological department of a large tertiary care center in Southern India. All clinically suspected ACDRs due to allopathic drugs, presented during two year period of all age groups and both sex were included in the study. A written informed consent was taken from patients and data were collected by means of pre-tested Performa including detailed clinical history, examination and relevant laboratory investigations. SPSS (Version 23.0) was used to obtain the results. Results: About 46% were between age group of 19–40 years. Majority were female (54%). 59% had generalized lesions, 98% had cutaneous manifestations, and 30% had mucous involvement. Itching was the most common presenting feature (48%). However, only 6% patients were asymptomatic. Most common etiological group of drugs responsible for ACDRs are antibiotics (27%) and NSAIDs (19%) pointing toward its rampant use with and without prescription. Among the Antibiotics, Ciprofloxacin was noted to be the most common responsible for ACDR. Diclofenac was found be the most common NSAID followed by Ibuprofen and Ketorolac. Majority of ACDRs, that is, 72% comprised of probable ACDRsas per “Naranjo’s algorithm.” The most common type of lesions observed was plaques (29%), macules (19%), papules (6%), and edema (6%). A predominant pattern of correlation was noted between antibiotics and erythematous drug eruption, SJS, vasculitis, erythroderma, and AGEP. The most common clinical pattern of ACDR observed was Urticaria (19%), Fixed Drug Eruption (13%), Erythema Multiforme (9%), and Lichenoid drug eruption (8%). Conclusion: The significance of this study was to study the profile of ACDR and to emphasize the awareness to the health-care providers on vigilant monitoring of ADRs and promptly reporting the same to prevent the occurrence of reactions in the vulnerable population. A systemic comprehensive monitoring and documentation of ADRs can curtail many untoward reactions in patient care and will lead to an effective drug administration. More studies are essential to create awareness of possible ACDR and to assist in the early recognition which, in turn, aids in the implementation of effective drug safety measures.